Introduction to transportation security - Edwards, Frances L.; Goodrich, Daniel C. (CRC Press, 2013)
Overview: Transportation is the lifeline of any nation, connecting people, supporting the economy, and facilitating the delivery of vital goods and services. The 9/11 attacks-and other attacks on surface transportation assets, including the bombings in Madrid, London, Moscow, and Mumbai-demonstrate the vulnerability of the open systems to disruption and the consequences of the attacks on people, property, and the economy. Now more than ever, it has become imperative for businesses operating in the transportation and transit sectors to develop comprehensive security programs accounting for both natural and man-made hazards and safeguarding people, places, and equipment-while at the same time ensuring operations continuity. Providing transportation managers with the knowledge, skills, and abilities to effectively manage the security of transportation assets, Introduction to Transportation Security examines: Basic theories of security and emergency management; The integrated nature of the nation's critical infrastructure and the threats to transportation in each surface mode; Federal agencies working in emergency management and transportation security and their intelligence and response requirements and capabilities; The types of disasters that have occurred in the U.S. and selected nations, and their significant economic impacts; Cost-beneficial security strategies aimed at preventing catastrophic failures in each transportation mode; Effective methods for organizing, testing, and evaluating transportation security across modes and professions; The book covers all transportation modes and their interconnectivity-including highway, air cargo, freight and passenger rail, transit, and maritime. It presents learning objectives and discussion questions to test assimilation of the material and case studies to facilitate a practical understanding of the concepts. Introduction to Transportation Security provides essential information for students in transportation management programs and professionals charged with safeguarding the movement of assets within our interconnected transportation network.